2007
DOI: 10.1021/jp074419o
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Methane Hydrate from Experiment and Molecular Simulation

Abstract: A single-sided transient plane source technique has been used to determine the thermal conductivity and thermal diffusivity of a compacted methane hydrate sample over the temperature range of 261.5-277.4 K and at gas-phase pressures ranging from 3.8 to 14.2 MPa. The average thermal conductivity, 0.68 +/- 0.01 W/(m K), and thermal diffusivity, 2.04 x 10(-7) +/- 0.04 x 10(-7) m2/s, values are, respectively, higher and lower than previously reported values. Equilibrium molecular dynamics (MD) simulations of metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 58 publications
5
114
2
2
Order By: Relevance
“…With same technique, thermal conductivities of several other gas hydrates, such as tetrohydrofuran (THF) hydrate (Cortes et al, 2009), xenon hydrate (Krivchikov et al, 2006), HCFC-141b hydrate , and CFC-11 hydrate ) have been measured. Transient plane source (TPS) technique in double-and single-sided configurations has been used more recently to measure thermal conductivity of gas hydrates Li et al, 2010;Rosenbaum et al, 2007). This technique is based on the transient method and the needle probe, but it has a very small probe (Gustafsson et al, 1979(Gustafsson et al, , 1986.…”
Section: Thermal Conductivity Of Gas Hydratementioning
confidence: 99%
See 1 more Smart Citation
“…With same technique, thermal conductivities of several other gas hydrates, such as tetrohydrofuran (THF) hydrate (Cortes et al, 2009), xenon hydrate (Krivchikov et al, 2006), HCFC-141b hydrate , and CFC-11 hydrate ) have been measured. Transient plane source (TPS) technique in double-and single-sided configurations has been used more recently to measure thermal conductivity of gas hydrates Li et al, 2010;Rosenbaum et al, 2007). This technique is based on the transient method and the needle probe, but it has a very small probe (Gustafsson et al, 1979(Gustafsson et al, , 1986.…”
Section: Thermal Conductivity Of Gas Hydratementioning
confidence: 99%
“…With respect to temperature effect, many studies found that hydrates exhibit a glass-like temperature dependence of thermal conductivity (Andersson and Ross, 1983;Handa and Cook, 1987;Krivchikov et al, 2005Krivchikov et al, , 2006Ross et al, 1981;Ross and Andersson, 1982;Tse and White, 1988). Among these studies, the works of Krivchikov et al (2005Krivchikov et al ( , 2006 are interesting as they found that both methane and xenon hydrates show crystal-like temperature dependence below 90 K, while exhibiting glass-like behavior above 90 K. The effect of pressure has also been investigated by many groups (Andersson and Ross, 1983;Rosenbaum et al, 2007;Waite et al, 2007). Only weak pressure dependency was observed by them.…”
Section: Thermal Conductivity Of Gas Hydratementioning
confidence: 99%
“…Experimental measurements of thermal conductivity in (type I) methane hydrate exhibit a crystal-like temperature dependence below 90 K, with glass-like behaviour above this temperature [24], while similar low-temperature behaviour is observed in some semi-conductor clathrates [25]. In addition to various recent molecular dynamics (MD) studies estimating methane hydrate thermal conductivities [26][27][28][29][30][31][32][33][34], and those of other clathrates [29,34], progress has been made towards elucidating the underlying mechanisms governing thermal conduction in methane hydrates of various polymorphs [31][32][33]. It was found that a greater extent of damping in guest-host energy transfer in type I methane hydrates as higher temperatures (above 150 K), is responsible for the more glass-like temperature dependence of the thermal conductivity, whereas more harmonic energy transfer at lower temperatures results in the experimentally observed crystal-like behaviour [31][32][33].…”
Section: Introductionmentioning
confidence: 66%
“…The JACF was defined for 100 ps at 30 K, for 50 ps at 100 and 150 K and for 20 ps at 200 K and above; a sampling ratio of approximately 20:1 or higher is recommended for a robust definition of the ACF [26]. These durations were found to be more than sufficient to provide a reliable estimate of the thermal conductivity at each temperature: the JACF had decayed essentially to zero within less than a quarter of the sampled time scales, and oscillated about zero thereafter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation